Developing a Digital Tool to Assess Students’ Sustainability Literacy in Wetland Contexts - Ina Agustina; Apit Fathurohman; Hamdi Akhsan (Postgraduate, University of Mataram, 2025)
This study develops a digital assessment instrument on the Socrative platform to measure high school students’ sustainability literacy on global warming within wetland ecosystems, supporting SDG 13 (Climate Action). Using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the research involved: teacher needs analysis, design of 50 wetland-contextualized multiple-choice questions, validation by four environmental experts and three teachers, and trials with 125 students. Content Validity Ratio (CVR ≥ 0.99) confirmed 32 items as valid; 18 were revised for contextual alignment. The instrument showed very high reliability (Cronbach’s Alpha = 0.977), with 25 questions demonstrating good discrimination. While Socrative enhanced interactivity, teacher competence in digital tools requires improvement. The innovation lies in integrating understudied wetland contexts with sustainability literacy assessments, bridging technology (Socrative), local ecology, and SDG principles. Findings emphasize contextualized digital tools as catalysts for climate education and educator capacity building.